Energy Management and Audit of the Lighting and Air Conditioning System at the Teratak Buluh Grand Mosque, Pekanbaru City - Nasution, Fikri Fahlevi; Khotimah, Nur; Martin, Awaludin; Sihombing, Tikkos (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Riau, 2024)
Energy management and audits are important steps in improving a building's energy efficiency. Mosques, as centers of religious and social activities, often have significant energy requirements. The research methods used include field observations at the Teratak Buluh Grand Mosque, measuring energy consumption, and recommendations for saving energy use. The research results show that mosques have the potential for significant energy savings with recommendations for energy conservation opportunities that can be implemented by reducing the number of lamps used and the number of air conditioners. Previously, electrical power consumption at the Teratak Buluh Grand Mosque was 74,480.40 kWh/year with electricity costs reaching IDR 68,894,370/year. Meanwhile, electrical power usage after energy conservation opportunities (ECO) is 41,918.40 kWh/year with electricity costs of IDR 38,774,520/year, with an energy consumption intensity (IKE) value at the mosque of 13.49 kWh/m2/ month. Based on Permen No. 13 Tahun 2012 Tentang Penghematan Energi Listrik, this value is included in the fairly efficient energy consumption category.